Leader selection and service delivery in community groups: Experimental evidence from Uganda - Deserranno, Erika; Stryjan, Miri; Sulaiman, Munshi (Global Poverty Research Lab Working Paper, 2022)
In developing countries, NGOs and governments often rely on local community-based groups for the delivery of financial and public services. This paper provides causal evidence of how the design of rules used for group leader selection affects leader identity and shapes group service delivery. In collaboration with the NGO BRAC, we randomly assigned newly-formed Savings and Loan Groups to select their leaders using either (i) a procedure in which final outcomes are decided in a public discussion and (ii) a procedure in which final outcomes are decided in a private vote. Leaders selected with a private vote are found to be less positively selected on socioeconomic characteristics than those elected in the public procedure and at the same time more representative of regular group members. Furthermore, selecting more representative leaders — through a private vote — results in groups that are more inclusive towards poor members by giving them more credit and retaining them longer. Three years after their creation, vote groups are more inclusive than discussion groups, without becoming less economically efficient.